Inequality and Christian ethics - Hicks, Douglas A. (New studies in Christian ethics, 2000)
Inequality and Christian Ethics, first published in 2000, provides a moral and empirical analysis of contemporary social and economic inequality. Drawing on Christian social ethics, political philosophy, and development economics, the book seeks to create an interdisciplinary conversation that illuminates not only the contemporary realities and trends of inequality, but their moral significance as well. It is necessary to examine and understand inequality in various forms - which the book maps out - including disparity in income, education, and health as well as differentials based on race, ethnicity, gender, and nationality. The book draws in particular on the theological ethics of Gustavo Gutiérrez and H. Richard Niebuhr to provide a Christian ethical approach to inequality and well-being. It considers the 'capability approach' set forth by Amartya Sen, Nobel laureate in economics. Sen's framework helps Christians and other persons to add specificity to what the commitment to 'equality before God' would demand in social and economic relations.